Perang Salib - Basri, Muhammad; Nasution, Annisa Zakia; Fajri, Yasmina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Civilization cannot be separated from history. because stories are what define civilization. The spread of Islam continued to expand, led by the Umayyads and continued by the Abbasids. Islam spread widely throughout the world to the European continent. For seven centuries, Islam used war strategies to attack Europe, which resulted in wars known as the Crusades, namely events in the history of Islamic civilization during the classical period. Islamic sacrifices for the establishment of the islamic State. in the year too big. However, in the era of globalization, history can no longer be seen as merely a decoration of the past. therefore, in this article we will formulate a problem formulation starting from the understanding and background of the crusades.